An (un)usual teaching team - Chrissi Nerantzi; Haleh Moravej (PRISM)
In this article we (AUTHOR 2 ‘the nutrition lecturer’ and AUTHOR 1 ‘the academic developer’) outline our experience of working on a team taught module. Both had worked together on an undergraduate module the nutrition lecturer teaches and had undertaken some research together using playful approaches to module evaluations. When the nutrition lecturer invited the academic developer to co-develop and team teach the postgraduate module Nutrition in Practice she could not resist. Team-teaching in this case was a choice. A choice to collaborate and experiment together with creative approaches to learning and teaching and further develop practice through this process (Minett-Smith & Davis, 2019).